HAEMATURIA AND COLIC CORRELATION AS CLINICAL PREDICTORS IN URETERAL STONES PATIENTS AT UROLOGY OUTPATIENT UNIT SOETOMO HOSPITAL WITHIN JANUARY 2011 - DECEMBER 2015 PERIOD - Laksmana, Wisnu; Renaldo, Johan; Djojodimedjo, Tarmono (Indonesian Urological Association, 2017)
Objective: Determine the relationship between clinical symptoms of colic pain and haematuria as a predictor of ureteral stones incident at Dr Soetomo Hospital within a period of five years. Material & methods: This study is a descriptive analytic study using the sensitivity-specificity test with retrospective design. Data were collected from patient's medical records with a ureteral stone diagnosis at outpatient unit Dr Soetomo Hospital within 2011-2015. Results: Renal colic or ureter colic without haematuria had 88.32% specificity and 53.07% sensitivity in the incidence of ureteral stones at Urology Outpatient Unit Dr Soetomo Hospital within 2011-2015 period. Haematuria without colic complaint had 29.37% sensitivity and 90.17% specificity in the incidence of ureteral stones. Colic and haematuria compared with colic had 55.76% sensitivity for the incidence of ureteral stones and 70.09% specificity. While colic and haematuria compared with haematuria had a sensitivity of 77.41% for the incidence of ureteral stones and 65.92% specificity. Colic and haematuria compared to other complaints has a 58.77% sensitivity for ureteral stones incidence and 94.66% specificity. Conclusion: Colic and haematuria are clinical predictors that have a better value than the complaints of colic without haematuria and haematuria without colic, in the ureteral stones incident at Urology Outpatient Unit Dr Soetomo Hospital within 2011-2015 period. This is consistent with the literature that mentions prominent complaint in the incidence of ureteral stones is their colic pain caused by the stone through the ureteral passage, and followed by haematuria for their mucosal surface injury.